Unjuk Kerja Cool Box Berbasis Thermoelectric Cooler (TEC) Menggunakan Sirkulasi Pembuangan Kalor - Citra Zaskia Pratiwi; Iman Mawardi; Fikrul Haikal Tamami (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
This research discusses performance of cool box based on Thermoelectric Cooler (TEC) using circulation of heat dissipation. The advantage of implementing circulation of heat dissipation is optimize performance of cold side of peltier element. Cool box has capacity of 6L with the dimension of 45 x 36 x 26 cm. Circulation of heat dissipation consists of some components such as water block, radiator, and pump. While cooling components used are peltier element TEC1-12706, DC fan, and coldsink. The cool box temperature measurement results without load for ± 3 hours show coldsink temperature stably at 10°C and 16°C for room temperature. While the results of temperature measurement with 6L load show coldsink temperature stably at 15°C and room temperature of 20°C for ± 3 hours. Air volume flow rate for coldsink temperature circulator of 0,0640 m3/s and air mass flow rate of 0,0768 kg/s whereas air volume flow rate for heat dissipation fan of 0,0224 m3/s and 0,0269 kg/s for air mass flow rate.